2017
DOI: 10.3390/min7100200
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Scandium and Neodymium on Biochar Derived after Low-Temperature Pyrolysis of Sawdust

Abstract: Abstract:The objective of this study was to investigate the adsorption of two rare earth elements (REEs), namely scandium (Sc) and neodymium (Nd), on biochar produced after low temperature pyrolysis (350 • C) of wood sawdust. The biochar was characterized with the use of several analytical techniques, namely X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and thermogravimetric (TG) analysis, while the pH at point of zero charge (pH PZC ) was also dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…In the present study, the removal capacity of raw FA was also determined and found to be 38 mg•g −1 . However, the It was seen from the data that the pseudo-second-order model fits (R 2 values, 0.991-1) the experimental data very well for both the zeolites used, indicating that the reaction rate depended on the number of available active sites on the surface [32,49,50]. For the initial Cu(II) ion concentrations of 45 and 100 mg•L −1 , the removal capacity of ZFA1Na was 93 and 196 mg•g −1 , respectively; this capacity was significantly higher compared with the capacity (40-70 mg•g −1 ) calculated in an earlier study in which the removal of multiple metal ions, namely, Co(II), Cr(III), Ni(II), Zn(II), and Cu(II), was investigated with the use of zeolites [29].…”
Section: Evaluation Of Kinetic Modelsmentioning
confidence: 89%
See 1 more Smart Citation
“…In the present study, the removal capacity of raw FA was also determined and found to be 38 mg•g −1 . However, the It was seen from the data that the pseudo-second-order model fits (R 2 values, 0.991-1) the experimental data very well for both the zeolites used, indicating that the reaction rate depended on the number of available active sites on the surface [32,49,50]. For the initial Cu(II) ion concentrations of 45 and 100 mg•L −1 , the removal capacity of ZFA1Na was 93 and 196 mg•g −1 , respectively; this capacity was significantly higher compared with the capacity (40-70 mg•g −1 ) calculated in an earlier study in which the removal of multiple metal ions, namely, Co(II), Cr(III), Ni(II), Zn(II), and Cu(II), was investigated with the use of zeolites [29].…”
Section: Evaluation Of Kinetic Modelsmentioning
confidence: 89%
“…The linearized kinetic models investigated in this study were the pseudo-first (Equation ( 3)) and pseudo-second-order models (Equation ( 4)) [31,32]. log(q e − q t ) = log q e − k 1 t 2.303…”
Section: Kinetic Studiesmentioning
confidence: 99%
“…carboxylic, phenolic, and lactonic) on their surface, due to their amphoteric nature [37]. Those groups might be responsible for the pseudocapacitive reactions observed.…”
Section: Electrochemical Performance Of Activated Biocharsmentioning
confidence: 98%
“…In relation to pHPZC results, both activated biochars had the point of zero charge in the acid range. The pHPZC indicates the electrokinetic behavior of the material, which usually varies with the properties of the precursor and the type and temperature of pyrolysis [37]. The acid pHPZC means that mostly acid functional groups are connected to both materials' surface, but KOHBWB, having a much lower pHPZC (2.86),…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…The presence of polar groups on the surface of FA-H 2 O 2 is likely to give a considerable cation exchange capacity to the sorbents. The point of zero charge (PZC) was determined using the suspension and potentiometric titration methods [44,45]. In the case of FA/FA-H 2 O 2 , the value was found to be about 8.1/8.3.…”
Section: Influence Of Phmentioning
confidence: 99%